LIGHT AND ELECTRON MICROSCOPIC EXAMINATION OF PINEAL GLAND - Kuş, İlter; Özen, Oğuz Aslan (Fırat University, 2001)
Aim: The aim of this study was to investigate the pineal gland of rat at light and electron microscopic level. Material and Method: For this purpose adult male Wistar albino rats were used. All animals were killed by vascular perfusion. The pineal glands of rats were removed, then processed for light and electron microscopy. Results: It was observed that the pineal gland was externally covered by a capsule and also contained abundant capillaries. In parenchyma of the gland, the two main type of cells observed were pinealocytes and glial cells. These cells were differentiated according to their nuclear staining characteristics. The nucleus of pinealocytes was large, euchromatic and notched, their cytoplasm had mitochondria and rich from lipid droplets and also granular endoplasmic reticulum sacs, golgi complex and many ribosomes were observed. Glial cell nucleus was stained dark because of chromatin intensity, mitochondria, lipid droplets, rough endoplasmic reticulum sacs were present in the cytoplasm. These cells were observed to have cytoplasmic extensions. Conclusion: Pinealocytes and glial cells were observed in the pineal gland of rat.

Amaç: Bu çalışma sıçan pineal bezinin ışık ve elektron mikroskop düzeyde incelenmesi amacıyla yapıldı. Gereç ve Yöntem: Bu amaçla Wistar-Albino cinsi erkek sıçanlar kullanıldı. Bütün hayvanlar vasküler perfüzyonla öldürüldü. Sıçanların pineal bezleri çıkartıldıktan sonra ışık ve elektron mikroskobik prosedürlerden geçirildi. Bulgular: Pineal bezin dıştan bir kapsülle çevrili olduğu ve bez yapısının bol miktarda kapiller içerdiği görüldü. Bezin parankimasında pinealositler ve glia hücreleri olmak üzere iki tip hücre gözlendi. Bu hücreler çekirdeklerinin boyanma özelliklerine göre ayırt edildiler. Pinealosit çekirdeklerinin ökromatik, iri ve çentikli olduğu, hücre sitoplazmasının mitokondri ve lipid damlacıklarından zengin ayrıca granüllü endoplazmik retikulum kesecikleri, golgi kompleksi ve çok sayıda ribozom içerdiği gözlendi. Glia hücre çekirdeklerinin kromatin yoğunluğundan dolayı koyu renkte boyandığı, hücre sitoplazmalarında da mitokondriler, lipid damlacıkları ve granüllü endoplazmik retikulum keseciklerinin bulunduğu gözlendi. Bu hücrelerin sitoplazmik uzantılara sahip oldukları görüldü. Sonuç: Sıçan pineal bezinde pinealositler ve glia hücreleri gözlendi.
PİNEAL BEZİN IŞIK VE ELEKTRON MİKROSKOP DÜZEYDE İNCELENMESİ